Distribution of Losses From Large Terrorist Attacks Under the Terrorism Risk Insurance Act - Carroll, Stephen J.; LaTourrette, Tom; Chow, Brian G.; Jones, Gregory S.; Martin, Craig (RAND Corporation, 2023)
The pending expiration of the Terrorism Risk Insurance Act (TRIA) of 2002 is the impetus for this assessment of how TRIA redistributes terrorism losses. The authors find that the role of taxpayers is expected to be minimal in all but very rare cases and that, even with TRIA in place, a high fraction of losses would go uninsured in each of the attack scenarios examined.